2023
DOI: 10.1039/d3sc04962k
|View full text |Cite
|
Sign up to set email alerts
|

Optimization strategies of high-entropy alloys for electrocatalytic applications

Liyuan Xiao,
Zhenlu Wang,
Jingqi Guan

Abstract: High-entropy alloys (HEAs) are expected to become one of the most promising functional materials in the field of electrocatalysis due to their site-occupancy disorder and lattice order. The chemical complexity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…However, the use of HEA NPs is still controversial as the methods for optimization of their structure and properties need to be improved. 214 Experimental techniques allow the synthesis of high-entropy carbides in the form of nanometer-sized particles. 215,216 The atomic structure of such nanoparticles is even more complex than that of HEAs containing metallic and non-metallic atoms that influence the catalytic activity of the active sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of HEA NPs is still controversial as the methods for optimization of their structure and properties need to be improved. 214 Experimental techniques allow the synthesis of high-entropy carbides in the form of nanometer-sized particles. 215,216 The atomic structure of such nanoparticles is even more complex than that of HEAs containing metallic and non-metallic atoms that influence the catalytic activity of the active sites.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy to achieve higher stabilization is the expansion to multinary compositions. 6,7 This method forms thermodynamically more stable alloys or bonds by adding elements that can alter electronic structures and act as stabilizing additives. 8 The incorporation of Mn into the spinel lattice of Co 3 O 4 can extend the catalyst lifetime by two orders of magnitude without compromising any activity during acidic OER.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-doped carbon materials have attracted considerable attention in the field of CO 2 RR because of their adjustable pore structure, high specific surface area, and good electrochemical stability. [32][33][34][35][36][37] Especially in the study of M-N-C catalysts based on metal elements such as Cu, Ni, Fe, and Co, etc., it has been demonstrated that these catalysts have high activity and selectivity for the reduction of CO 2 to CO. [38][39][40][41][42] Among the various reported metals, the carbon-loaded Cu-based catalyst shows high activity in CO 2 RR. [43][44][45][46] These reported catalysts are of particular interest because of their ability to generate large amounts of hydrocarbons, including HCOOH, CH 4 , C 2 H 4 , etc.…”
Section: Introductionmentioning
confidence: 99%